Nghiên cứu quá trình chuyển hóa dầu vi tảo thành biodiesel trên các hệ xúc tác dị thể lưỡng chức năng MCS - Toàn, Nguyễn Đăng; Diệu Hồng, Nguyễn Khán (Vietnam Journal of Chemistry, 2016)
Biodiesel was synthesized from microalgal oil typed Botryococcus using a bi-functional heterogeneous catalyst mesoporous calcium containning silicate (MCS). The microalgal oil owned a very large amount of free fatty acid. The conditions for the reactions were controlled such as temperature, time, catalyst dosage, methanol/oil molar ratio and agitation speed. The results revealed that the optimum conditions should be temperature of 63 oC, reaction of 24 hours, catalyst dosage of 5 %wt, methanol/oil molar ratio of 45/1 and stirring speed of 450 rpm. The conversion of the reactions was 95.3 %. Keywords. Biodiesel, mesoporous calcium containing silicate, bi-functional catalyst.